Pre-Seed, Seed, and Start-Up Business on the Vegetable Seller e-Commerce User in Bali Province - Arisena, Gede Mekse Korri; Ustriyana, I Nyoman Gede; Trisna, Anak Agung Inten (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Today, many efforts prepared to improve the scope of the agricultural commodity product marketing segment to make the consumer and farmer could enjoy it properly. One of those effort completed by building an e-Commerce based agricultural trading system. This study aimed to assess the pre-seed, seed and start-up business on the vegetable seller e-Commerce user in Bali Province. This study done on the e-Commerce platforms: Facebook, Instagram, Tokopedia, and Shopee that used by the vegetable seller e-Commerce user in Bali Province. There were 30 participants involved in this study. Qualitative descriptive analysis with simple data tabulation used to address the study aim. Results showed that the pre-seed business developed due to the owner’s hobby in the agricultural area and environmental factors that drove them to run an agribusiness. On the step of the seed business, the vegetable seller started the business according to their will. Most of the sellers still used social media-based e-commerce with a simple application module. They expect to develop a complete module system to run their e-Commerce based business in the future.